The Comparison Of Arbitration Dispute Resolution Process Between Indonesian National Arbitration Board (BANI) And London Court Of International Arbitration (LCIA) (Journal of Private and Commercial Law, 2022)
Arbitration is a way of resolving a civil dispute outside the general court based on an arbitration agreement made in writing by the disputing parties. Each country has a different settlement process. In Indonesia arbitration is based on Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. The Indonesian National Arbitration Board (BANI) is an agency established by the Indonesian government for law enforcement in Indonesia in resolving disputes or differences of opinion that occur in various trade, industrial and financial sectors. Likewise in Indonesia, in England there is also an Arbitration Board called LCIA which is one of the oldest arbitration institutions in the world and has resolved 303 cases annually. This agency acts autonomously and independently in upholding law and justice. The purpose of this research is to determine the differences in the dispute resolution process through arbitration in Indonesia and the UK. The research method used in this article is normative legal research and through a literature study approach with secondary assessment of legal materials and juridical data analysis. The results prove that the process and procedures for dispute resolution at the LCIA institution are different from the BANI institution in the process and procedures. as well as the legal basis used in resolving the parties' business disputes.